2011
DOI: 10.1080/09575146.2011.599794
|View full text |Cite
|
Sign up to set email alerts
|

Consensus or dissensus? Stakeholders’ views on the role of play in learning

Abstract: Across cultures and eras, children have engaged in play as part of the process of growing and maturing into adulthood. Play has been recognized as an effective form of pedagogy to promote learning in the early years. However, beliefs about what play is and how it should be practiced vary across Hong Kong and in other countries. Because Chinese culture places a heavy emphasis on academic achievement, a play-based curriculum has not been widely implemented in the region. Through classroom observations and interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 32 publications
(27 reference statements)
3
65
0
Order By: Relevance
“…Fleer (2010) suggested that most activities young children engaged in can be categorised as play. Being abstract, play is often defined by its forms, contexts, times, and philosophical orientation (Fung & Cheng, 2012). For example, Fung and Cheng (2012) described play as having clear goals and loss of self-consciousness with intrinsic motivation.…”
Section: Introductionmentioning
confidence: 99%
“…Fleer (2010) suggested that most activities young children engaged in can be categorised as play. Being abstract, play is often defined by its forms, contexts, times, and philosophical orientation (Fung & Cheng, 2012). For example, Fung and Cheng (2012) described play as having clear goals and loss of self-consciousness with intrinsic motivation.…”
Section: Introductionmentioning
confidence: 99%
“…In Hong Kong, Southeast Asia, academics have voiced apprehensions about the 'tremendous downward pressure' on early years' settings to adopt a target-oriented and formal academic curriculum, driven partly by parental demands to prepare children for admission into selective primary schools in a highly competitive education system (Chan & Chan, 2003, Fung & Cheng, 2012. Research undertaken by Fung and Cheng (2012) for example, reports on emerging tensions in regards to the role of early years education where parental expectations of schooling for their preschool children in Hong Kong are in conflict with government policies for early years education and pedagogy. The study shows that parents in Hong Kong perceive preschools as essentially a head start for the primary school system.…”
Section: The International Contextmentioning
confidence: 99%
“…Although there has been a shift in policy to more play based pedagogies, many Chinese teachers have difficulties implementing a play-based curriculum and resort to developing teacher-led playoriented pedagogies (Hua cited in Vong, 2012). The teaching style has been to reveal a transmission model of teaching and learning, with play being used as a mechanism for transmitting knowledge (Fung & Chen, 2012). In the traditional pedagogies children are expected to do the same thing at the same time and rarely work independently or in small groups on self-selected tasks (Vaughan, 1993).…”
Section: Enacting Play In Asian Early Childhood Curriculummentioning
confidence: 99%